Exploring GDPR compliance over provenance graphs using SHACL - Lewis, David; O'Sullivan, Declan; PANDIT, HARSHVARDHAN JITENDRA (My University, 2018)
Semantic web technologies provide an open and adaptable framework for compliance regarding the General Data Protection Reg- ulation (GDPR). Our previous work in this regard demonstrates the use of SPARQL for querying provenance of consent and personal data lifecycles for compliance. We extend this work through our model for evaluation of GDPR compliance using SHACL to validate the correct- ness and completeness of information. The model describes the creation of a compliance graph consisting of information required to document and demonstrate compliance linked to specific articles and obligations within the GDPR using the GDPRtEXT vocabulary.
SEMANTiCS 2018 ? 14th International Conference on Semantic Systems
Keywords: GDPR; Regulatory compliance; Provenance; SHACL